Sea level adaptation decisions under uncertainty. Issue 10 (8th October 2017) - Thorarinsdottir, T. L.; Guttorp, P.; Drews, M.; Kaspersen, P. Skougaard; de Bruin, K.
Abstract: Sea level rise has serious consequences for harbor infrastructure, storm drains and sewer systems, and many other issues. Adapting to sea level rise requires comparing different possible adaptation strategies, comparing the cost of different actions (including no action), and assessing where and at what point in time the chosen strategy should be implemented. All these decisions must be made under considerable uncertainty—in the amount of sea level rise, in the cost and prioritization of adaptation actions, and in the implications of no action. Here we develop two illustrative examples: for Bergen on Norway's west coast and for Esbjerg on the west coast of Denmark, to highlight how technical efforts to understand and quantify uncertainties in hydrologic projections can be coupled with concrete decision‐problems framed by the needs of the end‐users using statistical formulations. Different components of uncertainty are visualized. We demonstrate the value of uncertainties and show for example that failing to take uncertainty into account can result in the median‐projected damage costs being an order of magnitude smaller. Key Points: Decisions on adaptation measures need to take careful account of all uncertainties Modeling local sea level rise is essential Decisions under uncertainty do not have to be based on precise damage costs